THE ROLE OF THE FAMILY HEALTH STRATEGY NURSE IN ASSISTING THE ELDERLY WITH ALZHEIMER’S (REMUNOM, 2023)
The number of people with appearance in the world is approximately 50 million, with a predominance in the elderly population, the most common cause of which is Alzheimer's disease. The Family Health Strategy, where the nurse has the role of coordinating actions, presents itself as a sector of Brazilian Primary Health Care, responsible for promoting comprehensive care to the population. With the increase in the number of cases of the disease, more specialized attention is needed to provide care to these patients, as well as the implementation of methods for health promotion. Therefore, the objective of this study was to identify the challenges that the FHS nurse faces when providing assistance to elderly people with Alzheimer's. The methodology used was of a qualitative nature, as for the means it will be a bibliographic review and as for the purposes it will be descriptive. In the end, considering that through the growth in the number of deaths from Alzheimer's, the importance of the ESF for caring for the elderly with Alzheimer's was soon confirmed and, consequently, the value of the role of nurses in this care process was perceived. It was also considered that the nurse faces several difficulties in the ESF, such as the high demand of patients in the UBS for care, overload of activities and lack of time to develop educational practices, which generates an impact on the comprehensive care provided to the elderly with Alzheimer's, as well as their family members and/or caregiver.